2019
DOI: 10.34218/ijaret.10.5.2019.002
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation on Expansive Soil in Conjunction With Egg Shell Powder and Rock Dust

Abstract: Expansive soils are problematic due to the presence and consequent effect of their clay mineral constituents, which makes them show the volume change characteristics. The expansive and shrinkage behavior makes expansive soils unsuitable for direct engineering application in their natural form. In an effort to make them more practicable for different engineering applications, various additives and techniques are employed to improve the soil properties. Stabilization of soil with lime, cement, bitumen are expens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
3
3
0
Order By: Relevance
“…Evidently, the synergistic interaction between ESA and SP demonstrates an even more pronounced capacity for reducing the swelling characteristics inherent in expansive clay. These findings align harmoniously with analogous outcomes in previous studies, as demonstrated by the works of Jain et al [29], Bapiraju and Prasad K [18], Blayi et al [20], and Carlina et al [28].…”
Section: Combined Effect Of Sp and Esasupporting
confidence: 92%
See 4 more Smart Citations
“…Evidently, the synergistic interaction between ESA and SP demonstrates an even more pronounced capacity for reducing the swelling characteristics inherent in expansive clay. These findings align harmoniously with analogous outcomes in previous studies, as demonstrated by the works of Jain et al [29], Bapiraju and Prasad K [18], Blayi et al [20], and Carlina et al [28].…”
Section: Combined Effect Of Sp and Esasupporting
confidence: 92%
“…This behavior is in line with expectations, as the substitution of clay content with SP, characterized by lower affinity for water molecules, underpins this observed decline. This phenomenon resonates with findings reported by Bapiraju and Prasad K [18] and Blayi et al [20], further underlining the congruence between observed behaviors and prior research in this domain.…”
Section: Effect Of Sp and Esa On Compaction Characteristicssupporting
confidence: 90%
See 3 more Smart Citations